Can an intradialytic snack model compensate the catabolic impact of hemodialysis?. (April 2021) - Martins, Vítor Sá; Adragão, Teresa; Aguiar, Leila; Fortes, Alice; Costa, Mónica; Borges, Nuno; Calhau, Conceição; Macário, Fernando
Summary: Background and aims: Hemodialysis (HD) has a catabolic effect caused by alterations in protein metabolism, increase in resting energy expenditure (REE) and protein needs due to inflammation, HD circuit blood and heat losses, protein losses to dialysate and HD filter membrane biocompatibility. We aim to determine, as a proof of concept, whether a standardized intradialytic snack model is adequate to compensate the catabolic impact of HD. Methods: Cross sectional analysis of patients' chosen intradialytic intake according to a snack model, at the day of blood sample collection of three different months. As targets for the compensation of the catabolic impact of HD, we considered 316.8kCal (1.32 (±0.18) kcal/min – 240' of HD) for the estimated increase in REE and at least 7 g of protein losses/HD treatment. Results: A total of 448 meals were analyzed, with 383 given during daytime shifts. No intolerances were registered. The mean nutritional profile of the daytime shifts intakes was 378.8 (±151.4) kcal, 13.5 (±7.2) g of protein, 676 (±334) mg of sodium (Na), 361.0 (±240.3) mg of potassium (K) and 249.3 (±143.0) mg of phosphates (P). We found that 68% of the meals provided an intake ≥316.8kCal and 82% a protein intake ≥ 7 g, with a significant association found between treatment shift and energy (p < 0.028), protein (p < 0.028), lipids (p < 0.004), Na (p < 0.004), K (p < 0.009) and P (p < 0.039) intakes. Conclusions: We found that this intradialytic snack model meets the target for the treatment-related increases in protein and energy needs. Although sodium intake was found to be high, potassium and phosphate intake was considered adequate.